«It cannot be considered a finished work». "Le donne di Messina" by Elio Vittorini (Prassi Ecdotiche della Modernità Letteraria, 2016)
The manuscripts of Elio Vittorini’s Le donne di Messina, archived in Centro Apice (University of Milan), permit to reconstruct the evolution of the novel, which is strictly connected to the evolution of Vittorini’s intellectual and cultural project from the Post-war years to the Economic Boom years. This paper is specifically focused on the epilogue of the novel, whose stratified revision from the first volume edition in 1949 to the last edition in 1964 allow to formulate some hypotheses about Vittorini’s writing and re-writing technique.
Keywords: Elio Vittorini; Donne di Messina; rewriting; variants; archives